John Steinbeck’s Travels with Charley: In Search of What Kind of America? - Carletto, Alice (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2021)
The American road narrative as a genre has had little consideration in the academic context. Those narratives were most of the time studied in a fixed way, linked to spiritual and internal journeys rather than actually analyzing the relationship between humans and the space they were travelling on. Similarly, the environment had scant consideration in literary works as well as in the academic debate at least until the nineties. The aim of this article is to provide an analysis of an American road narrative through an ecocritical and space-oriented approach, trying thus to display what is the relationship between humans and the environment within this specific American genre. This will lead to new insights on aspects of mobility/movement and place/space, being the latter not only strongly linked to the American road trip, but also representing important features in American history and culture. The American road narrative chosen for this analysis is John Steinbeck‟s Travels with Charley: In Search of America (1962), the result of the author‟s travels in his own country.